The Role of HMGB1 in the Pathogenesis of Type 2 Diabetes - Yanan Wang; Jixin Zhong; Xiangzhi Zhang; Ziwei Liu; Yuan Yang; Quan Gong; Boxu Ren (Journal of Diabetes Research)
Significance. With an alarming increase in recent years, diabetes mellitus has become a global challenge. Despite advances in treatment of diabetes mellitus, currently, medications available are unable to control the progression of diabetes and its complications. Growing evidence suggests that inflammation is an important pathogenic mediator in the development of diabetes mellitus. The perspectives including suggestions for new therapies involving the shift from metabolic stress to inflammation should be taken into account. Critical Issues. High-mobility group box 1 (HMGB1), a nonhistone nuclear protein regulating gene expression, was rediscovered as an endogenous danger signal molecule to trigger inflammatory responses when released into extracellular milieu in the late 1990s. Given the similarities of inflammatory response in the development of T2D, we will discuss the potential implication of HMGB1 in the pathogenesis of T2D. Importantly, we will summarize and renovate the role of HMGB1 and HMGB1-mediated inflammatory pathways in adipose tissue inflammation, insulin resistance, and islet dysfunction. Future Directions. HMGB1 and its downstream receptors RAGE and TLRs may serve as potential antidiabetic targets. Current and forthcoming projects in this territory will pave the way for prospective approaches targeting the center of HMGB1-mediated inflammation to improve T2D and its complications.